Pengaruh Media Corong Berhitung terhadap Kemampuan Berhitung Siswa di Kelas III Sanggar Bimbingan Muhammadiyah Kepong Malaysia - Dwiyanti, Alda Elfiyana; Nasution, Ismail Saleh; Sari, Suci Perwita; Saragih, M. Afiv Toni Suhendra (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Based on observations conducted at the Muhammadiyah Kepong Guidance Center, Malaysia. One of the causes of the problems faced is learning media that is less interesting and interactive. Many teachers still use traditional approaches that make students feel bored and less motivated, and have a negative view of mathematics subjects that are claimed to be difficult and confusing. The objectives of this study are 1) to analyze the effect of the counting funnel media used in students' numeracy skills. 2) to evaluate the improvement of mathematical numeracy skills in the multiplication material of grade III students at the Muhammadiyah Kepong Guidance Center, Malaysia. The results of the analysis show that the sig value (2-tailed) is 0.000, which means it is less than 0.05. Thus, H0 is rejected and Ha is accepted. These results indicate that the counting funnel media has a significant positive impact on improving students' numeracy skills, especially in multiplication material. The findings of this study confirm that the use of the counting funnel media has an effect on students' numeracy skills in grade III of the Muhammadiyah Kepong Guidance Center, Malaysia, thus indicating that the use of this media is very effective in improving students' numeracy skills.